Penerapan kerangka berpikir ilmiah dalam penyusunan karya mahasiswa - arrasy, hafsa (Maliki Interdisciplinary Journal, 2025)
The scientific thinking framework is an essential foundation in the preparation of student academic writing, as it ensures that the writing process is carried out systematically, rationally, and in an accountable manner. However, many students still struggle to apply scientific thinking due to limited understanding of research steps and proper reasoning structures. This article discusses the implementation of a scientific thinking framework in student writing, beginning with problem identification, data collection, information analysis, and concluding with the formulation of findings. The discussion also highlights the importance of scientific reasoning in meeting academic competency standards, which require students to think critically, logically, and systematically. The results of this analysis indicate that applying a scientific thinking framework helps students produce academic work that is more coherent, objective, and well-structured, while also enhancing their ability to understand academic problems more deeply. Therefore, the scientific thinking framework serves as a fundamental skill that students must master to support the quality of their academic writing and overall intellectual development.